2022
DOI: 10.1186/s41687-022-00473-8
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life and social determinants of health following COVID-19 infection in a predominantly Latino population

Abstract: Background As the COVID-19 pandemic evolves, more information is needed on its long-term impacts on health-related quality of life (HRQoL) and social determinants of health (SDoH). The aim of the study was to assess HRQoL and SDoH among a predominantly Latino population of COVID-19 survivors and to compare effects in Latinos versus non-Latinos. Methods This cross-sectional study consisted of a survey (in English and Spanish) of COVID-19 survivors f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 46 publications
2
9
0
Order By: Relevance
“…Despite extensive research documenting the role of adverse social determinants of health increasing risk of acute SARS-CoV-2 infection, there are limited prior data regarding associations between social determinants and Long COVID. Consistent with our study, one prior study found that financial concerns were associated with worse health utility and quality of life among those recovering from COVID-19 [ 27 ]. Similarly, an online survey-based study found that graduate education and urban residence were associated with lower odds of Long COVID [ 15 ].…”
Section: Discussionsupporting
confidence: 92%
“…Despite extensive research documenting the role of adverse social determinants of health increasing risk of acute SARS-CoV-2 infection, there are limited prior data regarding associations between social determinants and Long COVID. Consistent with our study, one prior study found that financial concerns were associated with worse health utility and quality of life among those recovering from COVID-19 [ 27 ]. Similarly, an online survey-based study found that graduate education and urban residence were associated with lower odds of Long COVID [ 15 ].…”
Section: Discussionsupporting
confidence: 92%
“…For instance, 90 days after the acute phase, patients exhibiting symptoms of Long COVID (such as fatigue, sadness, myalgia, joint pain, dyspnea, anxiety, and vertigo) had significantly poorer SF-36 ratings for physical function, vitality, mental health, and physical health [ 26 ]. Another study found that HR-QoL was substantially lower 8.1 (±3.2) months after the acute episode [ 27 ]. In both systematic review and meta-analysis studies, HR-QoL was considerably decreased in Long COVID-19 patients especially in those with fatigue and admission to critical care units, with up to 37% (95% confidence interval: 18 to 60%) of the patients exhibiting decreased HR-QoL [ 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, cluster 3 had the highest percentage of leaves of absence in our study. Financial concerns owing to symptoms have been reported to be associated with an increase in both anxiety and depression [19]. In addition, in a previous study, which investigated "post-COVID-19 status, unspecified" using the International Classification of Diseases, 10th revision, long COVID patients were skewed toward those living in areas of low poverty and unemployment [20].…”
Section: Discussionmentioning
confidence: 99%